Ways To Transform Corrupt Relations Using Ethical Mechanisms (Zien Journal of Social Sciences and Humanities, 2024)
This article analyzes the issue of addressing corruption through ethical principles. It explores strategies for reducing corruption through ethical mechanisms, highlighting the social, economic, and cultural aspects of this process. Additionally, the article discusses the role of education and upbringing, the significance of moral values, and the philosophical foundations of reducing corruption. The article includes practical recommendations for effectively implementing ethical mechanisms in the fight against corruption